Skipping breakfast and physical fitness among school-aged adolescents - Jingcen Hu; Zhifei Li; Sixuan Li; Hui Li; Sijia Wang; Shuyu Wang; Lei Xu; Delun Yang; Tiecheng Ruan; Hang Li; Shuo Han; Qinghai Gong; et al. (Clinics, 2020)
OBJECTIVES: This study explored the relationship between skipping breakfast and physical fitness in a group of school-aged adolescents in China. METHODS: This cross-sectional study from the Chinese National Surveillance on Students’ Constitution and Health (CNSSCH) survey in Ningbo, China, used a standardized questionnaire to assess the frequency of breakfast consumption. Physical fitness was measured through standing long jump, 50-m sprint, 1,000 (or 800)-m run, and vital capacity tests. Multiple linear regression analysis was used to investigate the relationship between the frequency of breakfast consumption and physical fitness. RESULTS: Our study included a total of 1,849 school-aged adolescents (aged 15.53±1.80 years). Among boys, non-breakfast-skippers had good scores for 50-m sprints, 1,000-m run, and vital capacity tests when compared with breakfast skippers (all p<0.05). Among girls, non-breakfast-skippers had a good scores for the standing long jump test compared with breakfast skippers (p=0.003). The multiple linear regression model showed that not skipping breakfast was positively associated with vital capacity (β=-173.78, p=0.004) and inversely associated with 50-m sprint (β=-0.12, p=0.018) and 1,000-m run times (β=-8.08, p=0.001) in boys. CONCLUSION: The results of this cross-sectional study revealed that skipping breakfast might be associated with lower physical fitness in Chinese adolescents aged 13-18 years, especially boys. Breakfast consumption should be promoted among Chinese school-aged boys.